2015
DOI: 10.1021/acs.analchem.5b00040
|View full text |Cite
|
Sign up to set email alerts
|

“Periodic-Table-Style” Paper Device for Monitoring Heavy Metals in Water

Abstract: If a paper-based analytical device (μ-PAD) could be made by printing indicators for detection of heavy metals in chemical symbols of the metals in a style of the periodic table of elements, it could be possible for such μ-PAD to report the presence and the safety level of heavy metal ions in water simultaneously and by text message. This device would be able to provide easy solutions to field-based monitoring of heavy metals in industrial wastewater discharges and in irrigating and drinking water. Text-reporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 24 publications
1
68
0
Order By: Relevance
“…6(d). From this Ni detection demonstration, we were able to detect as low as 150 μg/L of Ni concentration which shows two folds improvement with the previous report 36, 37 . This heavy metal assay demonstration proves that the C-µPAD enables us to use for silane functionalization which requires thermal condensation to form covalent bonds.…”
Section: Resultsmentioning
confidence: 51%
“…6(d). From this Ni detection demonstration, we were able to detect as low as 150 μg/L of Ni concentration which shows two folds improvement with the previous report 36, 37 . This heavy metal assay demonstration proves that the C-µPAD enables us to use for silane functionalization which requires thermal condensation to form covalent bonds.…”
Section: Resultsmentioning
confidence: 51%
“…Although this limit may not be achievable by naked eyes, the overall process from image taking to processing, as discussed above, is fairly straightforward and does not require sophisticated instrument other than a digital camera or a scanner and an image analysis software. Overall, the performance of the sensor suggested that it has good potential for real applications and is competitive with previous works ,…”
Section: Resultsmentioning
confidence: 79%
“…In addition, the unique capillary property of cellulose also resulted in the development of microfluidic paper‐based analytical devices (μPADs), which employed patterning process (mostly wax printing) to confine liquid samples into desired locations without the need of external pumping process. This has led to more sophisticated applications, enabling the fabrications of sensors with more complex mixing process for various kinds of analytes ranging from metal ions, to biomolecules ,,…”
Section: Introductionmentioning
confidence: 99%
“…24 With regard to Cr analysis using μPADs, several methods have been reported. [29][30][31][32][33] Alahmad et al 29 used wax-printed μPADs, and detected Cr III into natural water by chemiluminescence. Colorimetric detection, which was reported by Henry's group, [30][31][32] is simple, and gray scale intensity analysis is often carried out using image-processing software.…”
Section: Crmentioning
confidence: 99%